2017
DOI: 10.18869/acadpub.jafm.73.240.25348
|View full text |Cite
|
Sign up to set email alerts
|

CFD Transient Simulation of a Breathing Cycle in an Oral-Nasal Extrathoracic Model

Abstract: Knowledge of respiratory flow behaviour is important in many respiratory medical fields. The usefulness of numerical models in providing a better understanding of flow phenomena has made the Computational Fluid Dynamics (CFD) an indispensable research tool due to the difficulty of measuring in vivo data. In this research, the extrathoracic airways and the upper tracheobronchial region, trachea and main bronchus bifurcation were modelled. Oral and nasal breathing routes have been considered under steady and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
Order By: Relevance
“… What is the role of the oral cavity? Paz et al [ 172 ] investigated the distribution between nasal and oral breathing under steady and unsteady flow. Chen et al [ 173 ] concluded that the inclusion of the oral cavity in CFD simulations of steady and unsteady nasal cavity flow had very little impact.…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
See 1 more Smart Citation
“… What is the role of the oral cavity? Paz et al [ 172 ] investigated the distribution between nasal and oral breathing under steady and unsteady flow. Chen et al [ 173 ] concluded that the inclusion of the oral cavity in CFD simulations of steady and unsteady nasal cavity flow had very little impact.…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
“…In silico studies are further grouped according to their modelling approach, Navier-Stokes-or Lattice-Boltzmann-based, as well as the turbulence modelling approach employed (laminar, RANS, LES, DNS). The present study [118,160,172,194,223] Spalart-Allmaras [204,226,246] Reynolds stress model [83] LES and RANS-LES hybrid models [83,148,204,206,217,237,247] [159, [248][249][250] The present study DNS [83] Lattice-Boltzmann-based methods (in silico) [42,125,195,[251][252][253] [127]…”
Section: Modelling Approaches In In Silico Studiesmentioning
confidence: 99%
“…The following initial and border conditions were considered: ▪ Air assumed as incompressible fluid [9]. Figure 4 shows that the results are starting to converge towards a single PD value.…”
Section: Figure 2 Scheme Of the Orifice Plate Theoretical Modelmentioning
confidence: 99%
“…• What is the role of the oral cavity? Paz et al [172] investigated the distribution between nasal and oral breathing under steady and unsteady flow. Chen et al [173] concluded that the inclusion of the oral cavity in CFD simulations of steady and unsteady nasal cavity flow had very little impact.…”
mentioning
confidence: 99%